2015
DOI: 10.1073/pnas.1509757112
|View full text |Cite
|
Sign up to set email alerts
|

Choosing experiments to accelerate collective discovery

Abstract: A scientist's choice of research problem affects his or her personal career trajectory. Scientists' combined choices affect the direction and efficiency of scientific discovery as a whole. In this paper, we infer preferences that shape problem selection from patterns of published findings and then quantify their efficiency. We represent research problems as links between scientific entities in a knowledge network. We then build a generative model of discovery informed by qualitative research on scientific prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 205 publications
(179 citation statements)
references
References 61 publications
7
170
0
2
Order By: Relevance
“…2). Conservative strategies (15) serve individual careers well but are less effective for science as a whole. Such strategies are amplified by the file drawer problem (16): Negative results, at odds with established hypotheses, are rarely published, leading to a systemic bias in published research and the canonization of weak and sometimes false facts (17).…”
Section: Problem Selectionmentioning
confidence: 99%
“…2). Conservative strategies (15) serve individual careers well but are less effective for science as a whole. Such strategies are amplified by the file drawer problem (16): Negative results, at odds with established hypotheses, are rarely published, leading to a systemic bias in published research and the canonization of weak and sometimes false facts (17).…”
Section: Problem Selectionmentioning
confidence: 99%
“…Some of these elements were previously considered in literature, such as a model of spreading ideas in a group of multiple agents [11]. Other studies addressed techniques to optimize the exploration of a knowledge space [12][13][14]. Another important aspect of interest is knowing how the interactions among researchers impacts the discovery process.…”
Section: Introductionmentioning
confidence: 99%
“…[6,10,[14][15][16][17][18][19]). Typically, each node represents a concept while the edges stand for the relationship between them.…”
Section: Introductionmentioning
confidence: 99%
“…They found that rewards for high-risk innovation are not sufficient to compensate for the risk of not publishing, leading to few high-risk innovations. Rzhetsky et al (2015) built a generative probabilistic network model to trace how molecules are typically combined in biomedicine and chemistry research, and then estimated it with extracted content on the molecules mentioned in millions of papers and patents over the latter half of the twentieth century. They then discovered optimal strategies through simulation and compared them with historical modes of collective discovery to identify inefficiencies associated with science as it is currently organized.…”
Section: Collective Attention and Reasoning Through The Content Of Comentioning
confidence: 99%